Transverse and left colon volvulus in a child with cerebral palsy: a case report - Younis Al-Mufargi; Shiyam Al-Shaibani; Balqees Al-Mujaini; Mohsin Alriyami; Mostafa Mahmoud Hamad; Abdulmalik Al-Atar (Journal of Pediatric Surgery Case Reports, 2025)
Introduction: Colonic volvulus is an uncommon cause of intestinal obstruction in children, with sigmoid volvulus being the most frequently reported type. Transverse and left colonic volvulus is exceedingly rare, particularly in patients with underlying neuromuscular disorders such as spastic cerebral palsy (CP). Case presentation: A 10-year-old male child with a known history of spastic cerebral palsy (CP) presented to the emergency department with progressive abdominal distension for five days and urinary retention for two days. He had a history of chronic constipation and was on oral baclofen for the management of his spasticity. He was febrile (38 °C), tachycardic, and had a severely distended and tense abdomen. Abdominal imaging, including x-ray and computed tomography (CT) revealed grossly distended large bowel loops with no clear transition point, suggestive of large bowel obstruction. He was taken emergently to the operating room for an exploratory laparotomy. We found that the transverse and left colon had volvulized and had patchy ischemia. The right and sigmoid colon were healthy. We did a resection of the volvulized colon, followed by a primary colo-colic anastomosis. The patient's postoperative recovery was uneventful. He resumed enteral feedings on postoperative day 3 and was discharged home shortly afterwards. At the 6-week follow up he continued to do well and had regular bowel function. Conclusion: Volvulus of the transverse and left colon should be considered in children who develop a bowel obstruction, particularly in those with a history of chronic constipation and/or cerebral palsy.